Analisis kegagalan sprocket pada transmisi mobil Antawirya - Muhammad Farras Farshal; Sri Nugroho; Yusuf Umardani (Jurnal Teknik Mesin Indonesia, 2022)
Sprocket is one part of the transmission system commonly used in motor vehicles. In transmission system of the eco car Antawirya team from Diponegoro University also uses sprocket as one of its components. When starting first attempt of the race and do full throttle, the sprocket become failure since deformation happens on sprocket. The sprocket run into plastic deformation and then caused chain exiting its path and come off. The purpose of this study is to find the cause of fatigue that occurs by hardness test, chemical composition test and stress analysis. Sprocket use aluminum alloy 7075-T6 as a material. As a result of chemical composition testing, aluminum content is 97.3% which is more than the standard maximum limit of 91.4%. The percentage of zinc is 0.06% while the minimum limit of standard is 5.1%. There are also differences from other chemical elements such as magnesium and copper. The addition of that other elements serves to increase the strength of the material because Al 7075-T6 is well known as material with high strength. The results of stress analysis using ANSYS software found that the loading that occurred produce a Von-Mises stress of 392 MPa and yield strength of the material is 503 MPa, from that figure makes 1.28 a safety factor value and there should be no deformation on the sprocket. As a result of the hardness test, it is known that the value of hardness in the area close to deformation is 76.16 HV while the standard is 175 HV.